The feeding of heather (Calluna vulgaris) to Teladorsagia circumcincta infected lambs reduces parasitism but can detrimentally impact performance - Shepherd, F. (BioMed Central, 2025)
Gastrointestinal nematode (GIN) infections impact small ruminant health, welfare, and production across farming systems. Rising anthelmintic resistance and regulation of synthetic drug use in organic farming is driving research and development of sustainable alternatives for GIN control. One alternative is the feeding of plants that contain secondary metabolites (PSMs) e.g., proanthocyanidins (PA, syn. condensed tannins) that have shown anthelmintic potential. However, PSMs can potentially impair performance, arising from reduced palatability and thus intake, digestibility or even toxicity effects. In this study, we tested the trade-off between the antiparasitic and anti-nutritional effects of heather consumption by lambs. The impact of additional feeding of a nematophagous fungus (Duddingtonia flagrans) on larval development was also explored. Lambs infected with Teladorsagia circumcincta or uninfected controls, were offered ad libitum heather, or a control chopped hay for 22 days during the infection patent period. Eight days into the patent period, parasitised lambs were supplemented (or remained unsupplemented) with D. flagrans for a 5-day period. Performance and infection metrics were recorded, and polyphenol levels in the heather and control hay were measured to investigate their association with activity. The lambs consumed heather at approximately 20% of their dry matter intake, which was sufficient to exhibit significant anthelmintic effects via a reduction in total egg output (P = 0.007), compared to hay-fed lambs; the magnitude of the reduction over time in heather fed lambs was almost 10-fold compared to control lambs. Negative effects on production were shown, as heather-fed lambs weighed 6% less than hay-fed lambs (P < 0.001), even though dry matter intake (DMI) of heather increased over time. D. flagrans supplementation lowered larval recovery in the faeces of infected lambs by 31.8% (P = 0.003), although no interactions between feeding heather and D. flagrans were observed (P = 0.337). There was no significant correlation between PA, or other polyphenol subgroups in the diet and egg output, which suggests that any association between heather feeding and anthelmintic effect is not simply and directly attributable to the measured polyphenols. The level of heather intake in this study showed no antagonistic effects on D. flagrans, demonstrating the methods can be used in combination, but provide no additive effect on overall anthelmintic efficacies. In conclusion, heather feeding can assist to reduce egg outputs in infected sheep, but at 20% of DMI negative effects on lamb performance can be expected which may outweigh any antiparasitic benefits.